Distributed Control of Battery Energy Storage Systems for Voltage Regulation in Distribution Networks With High PV Penetration - Zeraati, Mehdi; Hamedani Golshan, Mohamad Esmail; Guerrero, Josep M. (IEEE transactions on smart grid, 2018)
The voltage rise problem in low voltage distribution networks with high penetration of photovoltaic (PV) resources is one of the most important challenges in the development of these renewable resources since it may prevent the maximum PV penetration considering the reliability and security issues of distribution networks. In this paper, the battery energy storage (BES) systems are used in order to solve the voltage rise during the peak PV generation as well as the voltage drop while meeting the peak load. A coordinated control strategy is proposed to regulate the charge/discharge of BESs using a combination of the local droop-based control method and a distributed control scheme which ensures the voltages of feeder remain within allowed limits. Therefore, two different consensus algorithms are used: the first algorithm determines the BESs participation in voltage regulation in terms of their installed capacity whereas the second one modifies the BESs performance in terms of their state of charge to prevent the excessive saturation or depletion of batteries. The proposed controller enables the effective use of storage capacity in different conditions. Finally, the simulation results based upon real data of a radial distribution feeder validate the effectiveness of this approach.